Upaya Peningkatan Edukasi Pasien Diabetes terhadap “DORMAN” (Diet, Olahraga, dan Monitoring Active, Normal) di Puskesmas Genteng Kulon Banyuwangi: Efforts to Enhance Diabetes Patient Education on “DORMAN” (Diet, Exercise, and Monitoring Active, Normal) at Puskesmas Genteng Kulon Banyuwangi - Prasetyo, Joko; Kusumawati, Prima Dewi; Haswita, Haswita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Abstract Diabetes Mellitus (DM) is a non-communicable disease with a rising prevalence, including in Indonesia. Effective management of diabetes is crucial to prevent serious complications; however, many patients still have a limited understanding of how to control their blood sugar levels. This community service program aims to assess the effectiveness of an educational program in improving patients' knowledge about diabetes management at Puskesmas Genteng Kulon, Banyuwangi. The academic program is presented in a simple, easy-to-understand approach called DORMAN (Diet, Exercise, and Monitoring Active, Normal). This program utilizes various educational media such as leaflets, posters, and blood sugar monitoring tools. A total of 46 participants who met specific criteria were involved in this program. Program evaluation was carried out using knowledge questionnaires, program satisfaction surveys, and blood sugar monitoring forms. The results of this program showed a significant improvement in patient knowledge: more than half of the patients (52.2%) who initially had insufficient knowledge improved to a good level (80.5%) after participating in the educational program. Additionally, the blood sugar levels of patients who were initially abnormal, totaling 28 patients (60.9%), improved, with 30 patients (65.2%) achieving normal blood sugar levels after the education. These findings emphasize the importance of education grounded in clear, applicable information for self-management of diabetes. This program is expected to have a positive impact on community-level efforts to prevent diabetes complications.